Drosophila Cdk4 is required for normal growth and is dispensable for cell cycle progression. - Meyer, C.A.; Jacobs, H.W.; Datar, S.A.; Du, W.; Edgar, B.A.; Lehner, C.F. (The EMBO Journal, 2000)
Complexes of D-type cyclins and cdk4 or 6 are thought to govern progression through the G(1) phase of the cell cycle. In Drosophila, single genes for Cyclin D and Cdk4 have been identified, simplifying genetic analysis. Here, we show that Drosophila Cdk4 interacts with Cyclin D and the Rb homolog RBF as expected, but is not absolutely essential. Flies homozygous for null mutations develop to the adult stage and are fertile, although only to a very limited degree. Overexpression of inactive mutant Cdk4, which is able to bind Cyclin D, does not enhance the Cdk4 mutant phenotype, confirming the absence of additional Cyclin D-dependent cdks. Our results indicate, therefore, that progression into and through the cell cycle can occur in the absence of Cdk4. However, the growth of cells and of the organism is reduced in Cdk4 mutants, indicating a role of D-type cyclin-dependent protein kinases in the modulation of growth rates.